2015
DOI: 10.1007/s40618-015-0371-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel SLC12A3 gene homozygous mutation of Gitelman syndrome in an Asian pedigree and literature review

Abstract: Genotype and phenotype vary significantly among GS patients. Male patients tend to experience more severe symptoms and poor treatment effect. Further large-scale population, animal, and molecular biology experiments are required to investigate the complexity of GS and to find a better treatment regimen for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To date, 453 mutations have been deposited in the Human Gene Mutation Database (HGMD, http://www.hgmd.cf.ac.uk/ ). Interestingly, the phenotype of GS patients is highly heterogeneous [ 7 ]. Some researchers have analyzed the clinical and genetic characteristics in unrelated patients with GS.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 453 mutations have been deposited in the Human Gene Mutation Database (HGMD, http://www.hgmd.cf.ac.uk/ ). Interestingly, the phenotype of GS patients is highly heterogeneous [ 7 ]. Some researchers have analyzed the clinical and genetic characteristics in unrelated patients with GS.…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies have shown that female GS patients/carriers are much less severely affected than male GS subjects (6,7,23). As we have previously reported on a pedigree carrying a novel SLC12A3 gene homozygous mutation of GS in three patients with the homozygous mutation, the male proband also had more severe clinical symptoms and laboratory findings, and a poorer prognosis than the other two female relatives (14). These evidences suggest that gender may play a crucial role in phenotypic diversity.…”
Section: Discussionmentioning
confidence: 51%
“…Gene amplification was performed by polymerase chain reaction (PCR) of 3 ng/mL DNA samples with the Ion AmpliSeq™ Library Kit (Life Technology, USA). PCR was conducted using SLC12A3 primers (listed in Supplementary Table S1) on a GeneAmp 9700 PCR system (ABI) under the following conditions (8,12, 14): 5-min predenaturation and 30-s denaturation at 95°C, annealing at 57-64°C, and 90-s chain extension at 72°C; the above steps were recycled 30 times. All sample densities were of 3 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…To date, 488 mutations of the SLC12A3 gene have been discovered in patients with GS (HGMD, professional 2017.1), including missense mutations, shear mutations, nonsense mutations, and frame shift mutations, among which missense mutations are the most commonly described. Moreover, compound heterozygous mutations are more common than homozygous mutations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%